Classical Japanese prose an anthology - McCullough, Helen Craig (Stanford, California Stanford University Press, 1990)
"This volume brings together in convenient form a rich selection of Japanese prose dating from the ninth to the seventeenth centuries, a period during which the preeminent cultural and aesthetic values were those of the Heian court. It contains 22 works representing all the major indigenous literary forms, either complete or in generous excerpts, and is particularly rich in writing by women and in autobiographical writings. This anthology contains longer selections than the only other available anthology, which was published in the 1950s, and each selection is preceded by an introduction reflecting the most recent scholarship. With three exceptions, all the translations are by the compilers, and almost all of them are published here for the first time. Because of space limitations, the compiler has omitted the two long masterpieces of the age, The Tale of Genji and The Tale of Heike, which deserve to be read in their entirety, and which are available in paperback English translations. The book contains an extensive general introduction, thirteen illustrations, five maps, a glossary, and a selected bibliography of works in English translation."--Provided by publisher.
Includes bibliographical references (pages [575]-578).
Keywords: Japanese prose literature -- Heian period, 794-1185.; Japanese prose literature -- 1185-1600.